Open-access clinical trial registries: the Italian scenario - Mosconi Paola; Roberto Anna (Trials, 2012)
Abstract Background Citizens, patients and their representatives are increasingly insisting on working with health professionals to organize and discuss research protocols. The International Committee of Medical Journal Editors recommended setting up a public clinical trial registry where anyone can find key information about a trial. Around the world, governments have, in fact, now begun to legislate mandatory disclosure of all clinical trials. The aims of the present survey were to assess the availability of clinical trial registries for Italian citizens and to examine the transparency of the data items reported. Methods The availability of open-access clinical trial registries was surveyed on a sample of 182 websites, including research institutes and centers of excellence (IRCCS-teaching hospitals), hospitals and associations. For each registry we downloaded a sample of two trials to assess the correspondence of the data items reported. Results from the Italian and international registries were compared. Results Fifteen percent of the sample had an open-access registry of clinical trials. Comparison of the data items available, in terms of completeness and transparency, from institutional and international registries indicated wide variability. Conclusions Italian citizens, patients and their associations have scant access to local registries of clinical trials, and international registries are generally more informative. On the European level, advocacy and lobby actions are needed among citizens and patients to boost the diffusion of open-access clinical trial registries without language barriers, thereby facilitating participation, access to information, and the coordination of clinical research.